The Rorschach Inkblot Test : an interpretive guide for clinicians - Choca, James, 1945- (American Psychological Association, 2013)
"In this interpretive guide to the Rorschach Inkblot Test, James Choca describes the uses to which it is best suited. Used appropriately, the Rorschach uniquely reveals a person's level of energy, control of emotions, and thought processes--something that other tests are unable to do. Choca reviews the current literature, emphasizing those markers that have the strongest scientific support, and illustrates how to integrate the science and clinical art of Rorschach interpretation when working with patients. Case examples deftly illuminate these principles. After reading this book, graduate students and professionals will have acquired a solid foundation for administering and interpreting this constructive clinical tool"--Publicity materials. (PsycINFO Database Record (c) 2012 APA, all rights reserved).